2020
DOI: 10.1073/pnas.1915060117
|View full text |Cite
|
Sign up to set email alerts
|

The MYCL and MXD1 transcription factors regulate the fitness of murine dendritic cells

Abstract: We previously found that MYCL is required by aBatf3-dependent classical dendritic cell subset (cDC1) for optimal CD8 T cell priming, but the underlying mechanism has remained unclear. The MAX-binding proteins encompass a family of transcription factors with overlapping DNA-binding specificities, conferred by a C-terminal basic helix-loop-helix domain, which mediates heterodimerization. Thus, regulation of transcription by these factors is dependent on divergent N-terminal domains. The MYC family, including MYC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 73 publications
1
11
0
Order By: Relevance
“…Even at the lowest r value (≥0.5), transcription factor genes identified as specific to particular tissue-specific MPS populations made few additional connections, indicating that local adaptation is dependent on highly correlated and regulated expression of a small cohort of transcription factors. Nevertheless, associations that become evident at lower r values may identify combinatorial interactions in particular cell populations: Mycl , associated with DC fitness [ 152 ], was weakly correlated with Irf8 and Zbtb46 ; Cebpb with Nfil3 ; and interferon-related transcription factors ( Batf2 , Irf1/7/9 , Stat1/2 ) were connected at the threshold of 0.5 ( S3 Data ).…”
Section: Resultsmentioning
confidence: 99%
“…Even at the lowest r value (≥0.5), transcription factor genes identified as specific to particular tissue-specific MPS populations made few additional connections, indicating that local adaptation is dependent on highly correlated and regulated expression of a small cohort of transcription factors. Nevertheless, associations that become evident at lower r values may identify combinatorial interactions in particular cell populations: Mycl , associated with DC fitness [ 152 ], was weakly correlated with Irf8 and Zbtb46 ; Cebpb with Nfil3 ; and interferon-related transcription factors ( Batf2 , Irf1/7/9 , Stat1/2 ) were connected at the threshold of 0.5 ( S3 Data ).…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that either blocking mitochondrial pyruvate entry or inhibiting catalytic activity of ACLY corrected, though to different extent, the expression of genes characterizing hyperactivated DCs upon PP2Cd deletion (Figure 6L). The results showed that a network of signature genes including the activation and metabolism-related genes (il-6, il-1b, cd80, h2-iab, and ccr7), mitochondrial and glycolytic metabolism-related genes (pgc-1a, hk-2, and pkm2), and DC-specifying transcription factors (irf4, pu.1, c-myc, nr4a1, and nr4a3) (53)(54)(55)were substantially altered upon these treatments. We thus proposed that ACLY-driven metabolic-epigenetic flux, downstream of the PP2Cd/mTORC2 pathway, was critically involved in the gene program for DC identity.…”
Section: Pp2cd Mediates Metabolic-epigenetic Regulation Of Dcs Through the Mtorc2/acly Pathwaymentioning
confidence: 99%
“…Even at the lowest r value (≥ 0.5), transcription factor genes identified as specific to particular tissue-specific MPS populations made few additional connections, indicating that local adaptation is dependent on highly-correlated and regulated expression of a small cohort of TF. Nevertheless, associations that become evident at lower r value may identify combinatorial interactions in particular cell populations; Mycl, associated with DC fitness ( [135] was weaklycorrelated with Irf8 and Zbtb46; Cebpb with Nfil3 and interferon-related transcription factors (Batf2, Irf1/7/9, Stat1/2) were connected at the threshold of 0.5 ( Table S3).…”
Section: Clustering Of Transcription Factor (Tf) Expressionmentioning
confidence: 99%